Handbook of thermoset plastics - Goodman, Sidney H.; Hanna, Dodiuk (William Andrew, 2014)
Thermosetting plastics are a distinct category of plastics whose high performance, durability and reliability at high temperatures makes them suitable for specialty applications ranging from automotive and aerospace through to electronic packaging and consumer products (your melamine kitchen worktop is a thermoset resin!). Recent developments in thermoset plastics technology and processes has broadened their use exponentially over recent years, and these developments continue: in November 2011, French scientists created a new lightweight thermoset that is as strong and stable as previous materials yet can be easily reworked and reshaped when heated which makes it unique amongst thermosets and allows for repair and recycling. The Handbook of Thermoset Plastics, now in its 3rd edition, provides a comprehensive survey of the chemical processes, manufacturing techniques and design properties of each polymer, along with their applications.-Written by a team of highly experienced practitioners, the practical implications of using thermoset plastics are presented - both their strengths and weaknesses. The data and descriptions presented here enable engineers, scientists and technicians to form judgments and take action on the basis of informed analysis. The aim of the book is to help the reader to make the right decision and take the correct action - avoiding the pitfalls the authors' experience has uncovered. The new edition has been updated throughout to reflect current practice in manufacturing and processing, featuring: Case Studies to demonstrate how particular properties make different polymers suitable for different applications, as well as covering end-use and safety considerations. A new chapter on using nanoparticles to enhance thermal and mechanical properties. A new chapter describing new materials based on renewable resources (such as soy-based thermoset plastics).-A new chapter covering recent developments and potential future technologies such as new catalysts for Controlled Radical Polymerization. Goodman and Dodiuk-Kenig provide a comprehensive reference guide to the chemistry, manufacturing and applications of thermosets. Updated to include recent developments in manufacturing - from biopolymers to nanocomposites. Case Studies illustrate applications of key thermoset plastics.
Includes index.
Keywords: Thermosetting plastics -- Handbooks, manuals, etc.; elektronické knihy; electronic books